2021
DOI: 10.1111/eea.13099
|View full text |Cite
|
Sign up to set email alerts
|

Volatile chemical signals underlying the host plant preferences of Tuta absoluta

Abstract: The South American leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a serious pest of tomato causing substantial annual economic losses at a global scale. Our study comprised choice and no‐choice bioassays, aimed at understanding the preference of this oligophagous pest for a few selected solanaceous hosts (tomato, potato, eggplant, ashwagandha, black nightshade, wild tomato, tobacco, and datura), and the identification of the volatile cues that influence its host selection process. In choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(57 reference statements)
2
3
3
Order By: Relevance
“…Specifically, 15 VOCs were highly accumulated in tomato, with alcohol and heterocyclic compounds the most abundant. These results were different from the previous study, which reported that tomato had a higher number of terpenes and acid compounds than other host plants (including eggplant) (Msisi et al, 2021;Subramani et al, 2021). Our results showed that 24 VOCs were accumulated higher in eggplant with aldehyde and heterocyclic compounds the most abundant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Specifically, 15 VOCs were highly accumulated in tomato, with alcohol and heterocyclic compounds the most abundant. These results were different from the previous study, which reported that tomato had a higher number of terpenes and acid compounds than other host plants (including eggplant) (Msisi et al, 2021;Subramani et al, 2021). Our results showed that 24 VOCs were accumulated higher in eggplant with aldehyde and heterocyclic compounds the most abundant.…”
Section: Discussioncontrasting
confidence: 99%
“…Tuta absoluta is oligophagous and can survive and reproduce normally on potatoes, tobacco and other Solanaceae crops (Arnó et al, 2019). Nevertheless, it has been found that T. absoluta had a strong preference for tomatoes among host plants, and volatile chemical signals played important roles in its host plant preferences (Subramani et al, 2021). Similarly, in our previous study, it has been found that the number of eggs laid by T. absoluta was significantly higher on tomatoes than on eggplants (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 74%
“…All compounds identified in the present work are in accordance with literature data concerning the VOC released by tomato plants upon herbivore feeding (i.e. T. absoluta larvae) (Proffit et al 2011 ; Anastasaki et al 2015 , 2018 ; Catola et al 2018 ; Milonas et al 2019 ; Subramani et al 2021 ; Ayelo et al 2022 ; Deletre et al 2022 ; Miano et al 2022 ). In particular, we recorded a blend of volatiles emitted by tomato plants infested by Tuta larvae quantitatively different with respect to undamaged control plants as already reported (Anastasaki et al 2015 , 2018 ; Milonas et al 2019 ; Ayelo et al 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…Our results indicate that adult females of T. absoluta are attracted to Solanaceae host plant volatiles but avoid host plant volatiles in the presence of the non-host Asteraceae plants marigold, blackjack, and the positive control, wild tomato. These results are consistent with the fact that olfactory cues play an important role in the host finding process of T. absoluta ( Desneux et al., 2010 ; Bitew, 2018 ; Subramani et al., 2021 ). Our findings corroborate results of a previous study ( Miano et al., 2022 ), which demonstrated the host disruption and masking role of the volatiles of the positive control, wild tomato in the host location process of T. absoluta in the presence of the host plant cultivated tomato.…”
Section: Discussionsupporting
confidence: 89%